Techno-stress and Teachers’ Effectiveness in Private Secondary Schools in Education District V, Lagos State, Nigeria - Lawal, Rasaki Olanrewaju; Orunbon, Nurudeen Olalekan; Oyaleke, Kehinde Esther (Journal of Educational Sciences, 2025)
Techno-stress and teacher effectiveness in private secondary schools in Lagos State's Education District V were the main topics of this research. Four hypotheses were developed in order to provide a more comprehensive perspective of the study project. Simple random sample and a survey descriptive research design were used in the approach. The research included 348 private school teachers in Education District V, Lagos State, Nigeria. A total of 348 questionnaires were administered in the field; of these, 294 were deemed suitable for data analysis. The sample size for this investigation was obtained through stratified and purposive random sampling technique. The Techno-Stress Questionnaire (TSQ) and Teachers Effectiveness Questionnaire (TEQ) were the study tools used. Pearson Product-Moment Correlation inferential statistics were used to analyse the data. The findings obtained from the test of the four hypotheses show that techno-insecurity, techno-complexity, techno-overload and techno-uncertainty have negatively weak and significant relationship with teachers' effectiveness. It was concluded that that Techno-stress creators reduced teachers' effectiveness in private secondary schools in Education District V, Lagos State, therefore, there is a need to allay the fear of using technology among teachers. Therefore, the study recommends that teachers should undergo regular training with the use of technology to enable them to achieve results in less time.